LEVEL ACADEMIC BURNOUT IN FINAL LEVEL STUDENTS OF THE FACULTY OF MEDICINE MUSLIM UNIVERSITY OF INDONESIA - Ghassani Rivai, Andi Fauzan; Mokhtar, Shulhana; Harahap, Muhammad Wirawan; Amir, Suliati P; Aisyah, Windy N. (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Education is a primary need for a nation. As students, individuals are expected to be creative and independent. Many students experience pressure due to academic demands. This can cause fatigue or burnout syndrome, which is a condition where a person experiences emotional exhaustion, a tendency to depersonalize, and feelings of helplessness. This phenomenon is known as academic burnout. When students are under constant pressure, this can lead to burnout which is characterized by exhaustion, frustration, cynicism towards others, and a sense of uselessness. This study aims to determine the level of academic burnout in final year students at the Faculty of Medicine, Indonesian Muslim University. The design of this research is descriptive observational, where data collection is carried out over a certain period of time during the research. Research data was obtained from primary data using the School Burnout Inventory (SBI) questionnaire where the total sample for this study was 225 respondents. The results showed that 162 (72%) respondents experienced low levels of academic burnout, 35 (16%) experienced moderate levels of academic burnout, 27 (11%) did not experience academic burnout, and 1 (1%) respondent experienced high levels of academic burnout. Based on the research results, the personal inadequacy dimension has the highest average level compared to other dimensions.